Análises de fontes de fósforo na nutrição animal: técnicas nucleares e correlatas em estudos com coelhos - Artur Canella Avelar (2008)
The first goal of this study was to assess inorganic and radiological aspects of eight different phosphorus sources: calcinated bone meal (FAR), dicalcium phosphate (BIC), super triple phosphate (FST), super simple phosphate (FSS), monoammonium phosphate (FMA), sulphuramonium phoshphate (FSA), ammoniated calcium polyphosphate (POLI) and a bovine mineral supplement (SMB). Some toxic elements (As, Ba, F, Th and U) were identified in many products in significant levels. Natural radiation from the following radionuclides 226Ra, 228Ra and 40K present in the products were assessed. The results are examined in the light of standards for exposure adopted in some countries including from Brazil. Some products present radioactivity in high levels, specially super simple phosphate. The second aim of this project was to evaluate the zootecnic responses of using these products in feeding growing rabbits. To accomplish this goal, it was undertaken an experiment using White New Zealand rabbits. Young rabbits (48 males and 48 females) were taken in randomized blocks with 12 repetitions. Treatments were consisted on 98% of a basic diet plus 2% of each P source. Rabbits were fed from 30 to 72 days. Rabbits fed on high F content diets (400 ppm) presented a worse performance than other treatments. Further, animals from these groups presented the lowest liver weights and the highest fluorine content in rabbit longissimus dorsi tissue. Animals receiving fluoride high level contents (sulfide phosphate of ammonium and bovine mineral supplement) presented worst results of weight gain - BIC: 1449.5g; FAR: 1446.6g; FST: 1409.6g; POLI: 1370.0g; FMA: 1366.7g; FSS: 1320.5g; SMB: 1016.9g; FSA: 1009.1g - food consumption and conversion, and also the lighter livers amongst all animals from theexperiment - FSS: 75.2g; BIC: 70.1g; POLI: 69.9 g; FAR: 69.9g; FMA: 64.1g; FST: 60.3g; FSA: 47.0g; SMB: 46.9g what confirms the high toxicity that fluoride presents to this organ. Mineral profiles of longissimus dorsi tissue presented significant difference among treatments.